Gastrointestinal parasitoses discovered in agricultural workers in South Bohemia, Czechoslovakia - Stĕrba, J; Ditrich, O; Prokopic, J; Kadlcík, K (Folia parasitologica, 1988)
In the years from 1975 to 1982 1,750 persons, mostly employed by agricultural enterprises in the South Bohemian Region in Czechoslovakia, were examined. We discovered seven species of parasites: Taenia saginata in 0.3%, Enterobius vermicularis in 10.1%, Giardia lamblia in 1.0%, Endolimax nana in 0.8%, Entamoeba coli in 0.7%, Entamoeba hartmanni in 0.2%, and Chilomastix mesnili in 0.5%. The greatest number of parasites was found in students of the Secondary agricultural and technical school. Only two species of parasites were diagnosed in children of the employees. The incidence of E. vermicularis was 75% in children, in adult employees of agricultural enterprises, however, only 9.8%.
Keywords: Czechoslovakia; Feces; Československo; studenti; feces; Agricultural Workers' Diseases; Humans; Intestinal Diseases, Parasitic; Students; nemoci zemědělců; parazitární nemoci střev; dítě; lidé; Child